prove that
Cos A/1-Tan A - Sin A / 1-Cot A
= Sin A - Cos A
Answers
Answered by
4
Appropriate Question :
- Prove that :
⠀⠀⠀⠀⠀━━━━━━━━━━━━━━━━━━━⠀
Given :
Exigency To Prove :
⠀⠀⠀⠀⠀━━━━━━━━━━━━━━━━━━━⠀
Here ,
⠀⠀⠀⠀⠀⠀
- a² - b² = ( a + b ) ( a - b )
⠀⠀⠀⠀⠀━━━━━━━━━━━━━━━━━━━⠀
Therefore,
As, we can See that ,
- L.H.S = R.H.S
⠀⠀⠀⠀⠀
⠀⠀⠀⠀⠀━━━━━━━━━━━━━━━━━━━⠀
Answered by
2
Consider LHS,
We know,
and
So,
- LHS can be rewritten as
Additional Information:-
Relationship between sides and T ratios
sin θ = Opposite Side/Hypotenuse
cos θ = Adjacent Side/Hypotenuse
tan θ = Opposite Side/Adjacent Side
sec θ = Hypotenuse/Adjacent Side
cosec θ = Hypotenuse/Opposite Side
cot θ = Adjacent Side/Opposite Side
Reciprocal Identities
cosec θ = 1/sin θ
sec θ = 1/cos θ
cot θ = 1/tan θ
sin θ = 1/cosec θ
cos θ = 1/sec θ
tan θ = 1/cot θ
Co-function Identities
sin (90°−x) = cos x
cos (90°−x) = sin x
tan (90°−x) = cot x
cot (90°−x) = tan x
sec (90°−x) = cosec x
cosec (90°−x) = sec x
Fundamental Trigonometric Identities
sin²θ + cos²θ = 1
sec²θ - tan²θ = 1
cosec²θ - cot²θ = 1
Similar questions